Documentos oficiais do ensino de Língua Inglesa e sentidos-e-significados a eles atribuídos pelos professores de Inglês: entre o prescrito e o realizado - Luiz, Valkíria Bento (2015)
This research aims to analyze and contrast and senses-and-meanings attributed by English language teachers of the state's public school in Sao Paulo to official documents (Parâmetros Curriculares Nacionais de Língua Estrangeira, Orientações Curriculares do Ensino Médio e Currículo do estado de São Paulo). It is based on Learning Theories (MIILHOLLAN; FORISHA, 1972; Mizukami, 1986), the Socio- Historical- Cultural Theory (TSHC). (Vygotsky,1930/1998 and 1934/1999 and circle) and dialogical conception of language (BAKHTIN ,2004). The methodological approach is centered on content analysis (Bardin, 1977, 2011) and senses - and - meanings ((VYGOTSKY, 1930/1998; 1934/1999; 2001)) as a category of interpretation. It is hoped that this study will contribute with ideas and information about the reality of English language teaching in public schools in order to forward possible actions that take into account this complex reality